Supplementing routine hospital surveillance of malaria to capture excess mortality and epidemiological trends: a five-year observational study - Kabuya, Jean-Bertin Bukasa; Bond, Caitlin; Hauser, Manuela; Sikalima, Jay; Phiri, Bruce; Phiri, Dickson; Matoba, Japhet; Hughes, Jayme; Banda, Proscovia Miiye; Lupiya, James Sichivula; Chongwe, Gershom; Thuma, Philip E.; et al. (Frontiers in Malaria, 2024)
Malaria surveillance in Africa is conducted largely through health facility-based health management information systems (HMIS) which provide aggregated data to malaria control programs. Supplementation of HMIS surveillance with other routinely collected hospital data can provide vital statistics on malaria control in regions of high burden. To assess the utility of supplementing HMIS data, we implemented a pilot program of enhanced malaria surveillance in a district hospital in northern Zambia over a five-year period. Data were tabulated from existing nursing records, central pharmacy inventories, laboratory logbooks, and ward registers and cross-referenced with routinely collected HMIS data. The additional data collections captured excess malaria deaths resulting from pharmacy and blood bank stockouts (10.3 excess deaths/year) and revealed small but significant changes over time in the age distribution of patients that likely reflect underlying shifts in the local epidemiology due to malaria control programming or other factors (median age from 1.9 to 2.4 months old, P=0.001). Readily available data can supplement existing HMIS surveillance in high malaria burden areas to provide actionable information about the local epidemiology and impacts of control efforts. Excess malaria deaths due to health systems factors can be feasibly captured and tracked and fed back to national malaria control programs and the World Health Organization to present a fuller picture of malaria burden.